1987
DOI: 10.1248/cpb.35.668
|View full text |Cite
|
Sign up to set email alerts
|

New acyclic bis-phenylpropanoids from the aril of Myristica fragrans.

Abstract: From a methanolic extract of the aril of Myristica fragrans HOUTT. (mace), the following new threo and erythro acyclic bis-phenylpropanoids were isolated: threo -2-(4-allyl-2, 6-dimethoxyphenoxy)-1-(4-hydroxy-3-methoxyphenyl)propan-1-ol (la), erythro-2-(4-allyl-2,6-dimethoxyphenoxy)-1-(4-hydroxy-3-methoxyphenyl)-1-methoxypropane (2b), erythro-2-(4-allyl-2,6-dimethoxyphenoxy)-1-(4-hydroxy-3,5-dimethoxyphenyl)propan-1-ol (3b), 2-(4-allyl-2,6-dimethoxyphenoxy)-1-(4-hydroxy-3-methoxyphenyl)propane (4), erythro-2-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 1 publication
2
17
0
Order By: Relevance
“…In addition to those referred to in our previous paper (Wallis et al, 1991) further guaiacyl and syringyl ~-ether neolignans have been isolated. Thus several erythro-guaiacyl ~-ethers were found; 3a from Krameria cystisoides (Achenbach et al, 1987), 3b from Nardostachys jatamansi (Bagchi et al, 1991), and 3c and 3d from Myristica fragrans (Hattori et al, 1987). The threo-guaiacyl ~-ether 2c was isolated from Myristica fragrans (Hada et al, 1988 syringyl ~-ethers were obtained from Myristica fragrans, compounds 4a and 5b by Hattori et al (1987) and 5c and 5d by the same group .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to those referred to in our previous paper (Wallis et al, 1991) further guaiacyl and syringyl ~-ether neolignans have been isolated. Thus several erythro-guaiacyl ~-ethers were found; 3a from Krameria cystisoides (Achenbach et al, 1987), 3b from Nardostachys jatamansi (Bagchi et al, 1991), and 3c and 3d from Myristica fragrans (Hattori et al, 1987). The threo-guaiacyl ~-ether 2c was isolated from Myristica fragrans (Hada et al, 1988 syringyl ~-ethers were obtained from Myristica fragrans, compounds 4a and 5b by Hattori et al (1987) and 5c and 5d by the same group .…”
mentioning
confidence: 99%
“…Thus several erythro-guaiacyl ~-ethers were found; 3a from Krameria cystisoides (Achenbach et al, 1987), 3b from Nardostachys jatamansi (Bagchi et al, 1991), and 3c and 3d from Myristica fragrans (Hattori et al, 1987). The threo-guaiacyl ~-ether 2c was isolated from Myristica fragrans (Hada et al, 1988 syringyl ~-ethers were obtained from Myristica fragrans, compounds 4a and 5b by Hattori et al (1987) and 5c and 5d by the same group . Green et al (1991) recently reported the unusual erythro monomethoxy/~-ether 6 as a constituent of Piper capense.…”
mentioning
confidence: 99%
“…Moreover, empirically, the coupling constant of protons in the erythro-configuration is smaller than that in the threo-configuration. 10,11) Before gymnasterkoreayne E having large coupling constant (Jϭ4.1 Hz) was reported 3) as erythro-configuration by only comparison of coupling constant by literature, 12) but it might be assigned incorrectly due to the lack of both isomers. This time both isomers were isolated from the same plant and determined to configuration having large coupling constant as threo-and small coupling constant as erythro-.…”
Section: Resultsmentioning
confidence: 99%
“…M. fragrans is also prescribed for medicinal purposes in Asia to treat many diseases such as rheumatism, muscle spasm, decreased appetite, and diarrhea (Nguyen et al, 2010). It contains 25-30% fixed oils, 5-15% volatile oils, phenylpropanoids, lignans, and neolignans (Davis and Graham, 1982;Hattori et al, 1987;Hada et al, 1988) and has antitumor, antimicrobial, antiviral, antifungal, anti-atherosclerotic and anti-inflammatory properties (Orabi et al, 1991;Yang et al, 2006;Cho et al, 2007). Previously, novel dibenzylbutane lignan, 7-methyl ether dibenzylbutane lignan, and six known lignans, were characterized as LDL antioxidant agents from the seed of M. fragrans (Kwon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%